Pemanfaatan Media Sosial di Era Digitalisasi bagi Siswa-Siswi SMK Ass'adatul Abadiyah Muaragembong Kabupaten Bekasi - Bobby Reza; Ronald Parulian; Muhammad Junaid Kamaruddin; Sheila Silvia Permatasari; Martin Purnama Chandra; Melani Angelina; Ahmad Taohid (Yayasan REDI Tiga Monas, 2023)
The Tri Dharma of Higher Education requires 3 main pillars, teaching, research and community service. Community service aims to increase the dignity and status of the community in the intended place of service. Community Service was at Muara Gembong, Bekasi Regency. which are predominantly farmers and fishermen, has not fully utilized social media to improve their social life, this has encouraged the realization of community service activities. Aimed high school age with the hope that they will become pioneers of change and pioneers of improving the quality of life through social media. This social media utilization activity aims to provide knowledge and understanding both theoretically and practically regarding the use of social media in the era of digitalization to students of Ass'adatul Abadiyah Muaragembong Vocational School, Bekasi Regency. Through this training, it is hoped that it can provide provisions and prepare vocational school graduates who can immediately enter the digital business world by utilizing social media. The method implemented in the implementation of community service activities is by holding socialization activities, providing an understanding of the in and out of social media. The method of implementing this service begins with the preparation stage, providing material and practicing using social media.